The composition of blood and stress hormone of red tilapia (Oreochromis sp.) feed with spirulina enriched Artemia - Abdul Latip, Syahirah (2013)
Effect of Spirulina enriched Artemia of the Great Salt Lake strain on the blood composition and cortisol hormone (stress hormone) level of Oreochromis niloticus was studied. This experiment was conducted at Institute of Bioscience, University Putra Malaysia for 15 days. The Red tilapia about 14 days old were stocked into different treatment tanks, each tank filled with 11L of dechlorinated aerated tap water and 110 tilapia individuals. There were 4 different treatment tanks, each treatment consisted of 3 replicates. The treatments tested were T1 (unenriched Artemia), T2 (Artemia enriched with Spirulina for 3 hours), T3 (Artemia enriched with Spirulina for 6 hours) and T4 (Artemia enriched with Spirulina for 9 hours). The Artemia were then frozen before fed to the fish ad libitum three times per day. Level of cortisol hormone and blood composition were examined for their initial and final readings. The analyzed water quality parameters were water temperature, dissolved oxygen, pH and ammonia nitrogen rate. The result showed that both unenriched and enriched Artemia effected the blood composition and cortisol hormone level. Fish fed with Artemia enriched with Spirulina for 9 hours gave the highest blood composition reading as well as recording the lowest stress hormone level compared to other treatments.